Progesterone Enhances the Invasion of Trophoblast Cells by Activating PI3K/AKT Signaling Pathway to Prevent Preeclampsia - Liu, Hongyu; Yu, Ling; Ding, Yiling; Peng, Mei; Deng, Yali (Cell transplantation, 2023)
We aimed to explore whether the effect of progesterone on preeclampsia via the PI3K/AKT signaling pathway. First, we studied the role of progesterone in preeclampsia patients and HTR-8/Svneo cells by adding progesterone. Then PI3K inhibitor LY294002 was added. The effects of progesterone on preeclampsia were also studied in animals by constructing a preeclampsia rat model. CCK-8 and Transwell assay were applied to measure cell viability and invasion ability. ELISA was performed to measure progesterone, MMP-2, MMP-9, pro-inflammatory factors TNF-α, IL-1β, and anti-inflammatory factors IL-4, IL-10, and IL-13 levels. HE staining was used to detect the pathological changes in uterine spiral artery. Western blot was performed to detect Cyclin D1, PCNA, MMP-2, MMP-9, inflammatory factors TNF-α, IL-1β, IL-4, IL-10, IL-13, and PI3K/AKT signaling pathway related proteins AKT, p-AKT, PI3K, and p-PI3K expressions. Progesterone could reduce blood pressure and urine protein in pregnant women with preeclampsia. TNF-α and IL-1β levels were decreased, but IL-4, IL-10, IL-13, cyclin D1, and PCNA levels were increased in pregnant women with preeclampsia after using progesterone. After the use of progesterone, the symptoms of the PE model group were improved. Among them, the lumen of the placental uterine spiral artery was enlarged, and the fibrinoid necrosis of the uterine wall and acute atherosclerotic lesions were relieved. In addition, progesterone promoted HTR-8/Svneo cells proliferation and invasion. However, high expression of MMP-2, MMP-9, p-AKT, and p-PI3K in Normal and preeclampsia groups caused by progesterone was weakened after adding LY294002, indicating that progesterone could activate PI3K/AKT signaling pathway to regulate HTR-8/Svneo cells. Progesterone decreased urine protein and blood pressure of preeclampsia rats in a concentration-dependent manner. Moreover, progesterone activated the PI3K/AKT signaling pathway and inhibited the inflammatory response in preeclampsia rats.